2018
DOI: 10.11118/actaun201866030685
|View full text |Cite
|
Sign up to set email alerts
|

Colored Wheat: Anthocyanin Content, Grain Firmness, Dough Properties, Bun Texture Profile

Abstract: . In colored wheat was observed approximately seven times more content compared with the control. The highest firmness was obtained in purple (27.62 N) and the lowest in blue grain (22.31 N). The lowest stickiness was found in blue wheat dough and therefore, it would be more suitable for manufacturing. Blue wheat decreased the dough cohesiveness and work of adhesion. The crumb hardness was significantly lowest in blue batch (P < 0.01) in 100 and 90 % concentration and in 80 % mixture was control significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, buns prepared using blue grains showed the lowest crumb hardness and higher cohesiveness and are therefore believed to be less susceptible to crumbling. On the other hand, when the anthocyanin content in purple wheat increased to 47.63 mg/kg, dough stickiness increased and became unsuitable for processing (Král et al, ). Sroan and Kaur () found that addition of antioxidants slightly increased dough water absorption, which could be due to the fact that added ingredients compete with gluten proteins for water absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, buns prepared using blue grains showed the lowest crumb hardness and higher cohesiveness and are therefore believed to be less susceptible to crumbling. On the other hand, when the anthocyanin content in purple wheat increased to 47.63 mg/kg, dough stickiness increased and became unsuitable for processing (Král et al, ). Sroan and Kaur () found that addition of antioxidants slightly increased dough water absorption, which could be due to the fact that added ingredients compete with gluten proteins for water absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The overall quality of both breads was acceptable. Purple and blue wheat flours were successfully used in the production of buns, a type of bread roll used mainly in making sandwiches [ 43 ]. The doughs and buns were prepared with wholegrain flour from regular wheat, purple wheat, or blue wheat, either by itself (100%) or in combination with white flour (90/10 and 80/20).…”
Section: Purple Wheat Productsmentioning
confidence: 99%